Dramatic Dialogue And Its Effectiveness In Enhancing The Characteristics Of The Alienated Character In The Television Series (Al-Academy, 2023)
Dialogue is one of the pillars of character building in the television series, through which it is possible to identify the most important characteristics and traits of the personality, in addition to its ability to reveal the most important problems at all levels. The following: (How does dialogue contribute to enhancing the traits of the alienated personality?). It therefore aims to identify the effectiveness of the dramatic dialogue in enhancing the traits of the alienated personality represented by (powerlessness, isolation, meaninglessness, objectification, non-standardization and rebellion). (The traits of the alienated character, and the second is the psychological function of the dramatic dialogue), to extract from them the main indicator that will be based on the analysis process for the sample that was represented by the series (Will).Its alienation, if this feature coincides with other elements of the narrative that allow it to be sensed. The most important conclusions reached by the research were: that the alienated personality is aware of the state of alienation in which it lives, which is confirmed by its dramatic dialogue. While the research concluded with recommendations and suggestions, and then a list of sources and references on which it was based.